Assessment of the nutritional status and dietary practices of the adolescents in the urban field practice areas of Trichy SRM Medical College and Research Centre - Govindan, Sripriya; Kumarasamy, Hemalatha; V., Raghuram (International Journal Of Community Medicine And Public Health, 2023)
Background: Malnutrition is still prevalent globally with the coexistence of both overnutrition and undernutrition in developing countries affecting people of all ages. Adolescents are particularly at risk of malnutrition due to rapid growth and development and changes in dietary habit that influences their nutrient intake. Dietary and other lifestyle behaviors formed during adolescence contribute to adulthood behaviors. This study therefore aimed at assessing the dietary practices and nutritional status of adolescents in urban field practice areas of Trichy SRM Medical College and Research Centre. Methods: This wass a cross-sectional study with a sample size of 191, conducted in urban field practice areas of Trichy SRM Medical College and Research Centre. The adolescents (11 to 19 years) are the study participants, and a simple random sampling method was followed to recruit the study population. A pretested semi structured questionnaire containing variable details and anthropometric measurements were taken. The chi-square test was used to find the association between different variables and malnutrition. Results: Among the study population 137 (71.7%) of the adolescents have calorie deficits with 24 hours recall method of food intake. Among the study population, 138 (72.3%) have normal BMI, 2 (1%) were overweight, 29 (15.2%) were thin and 22 (11.5%) are very thin. Conclusions: Malnutrition is still persistent in the adolescent population which should to addressed with additional specific interventions focusing on this age group. Focused interventions to improve appropriate calorie intake are to be initiated at the community and school level.